Psycho-physiological predictors of ten-pin bowling performance among East Coast State Bowlers - Abdullah, Anis Syazwanie Wan (2018)
The aim of this study was to determine the individual psychophysiological markers for optimum ten-pin bowling performance. A total of 32 participants aged from 15 to 26 years old (M = 17.58, SD = 2.575) of Pahang state ten-pin bowling player were recruited. In this study, participants average experience in playing ten-pin bowling was M = 5.57 (SD = 3.131). Participants is asked to play 15 games where the heart rate will be measured, and they also need to answer few questionaires such as IZOF, CSAI-2R and DVT. The psychophysiological markers measured in this study were cognitive anxiety, somatic anxiety, self-confidence, concentration and heart rate. Multiple Linear Regression was used to calculated the prediction of ten-pin bowling performance (score) based on their arousal level, cognitive level, cognitive anxiety level, somatic anxiety level, self-confidence level, concentrarion, average strike per session, average spare per session and average miss per session. There were statistically significant different in all the psychophysiological markers (p < 0.001 and p < 0.05). The participants also had the highest heart rate when they missed their throw.